Whole Genome Sequencing of a Methicillin-Resistant Staphylococcus aureus Pseudo-Outbreak in a Professional Football Team. (4th November 2014) - Anderson, Deverick J.; Harris, Simon R.; Godofsky, Eliot; Toriscelli, Todd; Rude, Thomas H.; Elder, Kevin; Sexton, Daniel J.; Pellman, Elliot J.; Mayer, Thom; Fowler, Vance G.; Peacock, Sharon J.
Abstract: Two American football players on the same team were diagnosed with methicillin-resistant Staphylococcus aureus (MRSA) skin and soft tissue infections on the same day. Our investigation, including whole genome sequencing, confirmed that players did not transmit MRSA to one another nor did they acquire the MRSA from a single source within the training facility.